Homocysteine Impairs Endothelial Cell Barrier Function and Angiogenic Potential via the Progranulin/EphA2 Pathway - Tian, Dan; Qin, Qing; Li, Mingfei; Li, Xiaoyu; Xu, Qing; Lv, Qianzhou (Frontiers in Pharmacology, 2021)
Hyperhomocysteinemia is a well-recognized independent risk factor for cardiovascular disease. To date, the mechanism of pathological plasma homocysteine (Hcy) level elevation remains to be elucidated. We aimed to investigate the levels of progranulin (PGRN), Eph-receptor tyrosine kinase-type A2 (EphA2), vascular cell adhesion molecule-1 (VCAM-1), and Hcy in patients with arteriosclerosis and investigate their functions in Hcy-injured human umbilical vein endothelial cells (HUVECs). EphA2 knockdown was induced in HUVECs by shRNA lentivirus infection with EphA2-RNAi, and bulk RNA-seq assay was performed. Then we investigated the mechanism underlying the effect of recombinant human PGRN (rhPGRN) combined with shRNA interference of EphA2 on cell proliferation, migration, and angiogenesis in Hcy-injured HUVECs. Results showed that serum EphA2, VCAM-1, and Hcy levels in acute coronary syndrome patients were significantly higher than those in chronic coronary syndrome patients (P = 0.000; P = 0.000; P = 0.033, respectively). In vitro, we demonstrated that knockdown of EphA2 significantly impaired cell adhesion and inhibited HUVECs migration and angiogenesis (P < 0.001), which was associated with reduction in VCAM1 and VE-cadherin (P < 0.05). Hcy modulated the expression of PGRN and EphA2 in a time-and dose-dependent manner. However, rhPGRN ameliorated the Hcy-induced reduction in cell viability and migration (P < 0.05). Mechanistically, we found that PGRN/EphA2 and its downstream AKT/NF-κB signaling might be the primary signal transduction pathways underlying Hcy-induced injury. The present study illustrated that PGRN plays a previously unrecognized role in Hcy-induced endothelial injury, which is achieved through its interaction with EphA2 signaling, implying a promising therapeutic target for cardiovascular disease.